PENGGUNAAN METODE PEMETAAN PIKIRAN UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VIII - Ela Sulastri; Ine Rahayu Purnamaningsih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Singaperbangsa Karawang, 2022)
This research is focused on improving students' ability in writing descriptive text with the mind mapping method. Mind mapping is one of the methods of learning that focuses on taking notes that help us remember the material and can improve understanding of the material, help organize material and provide new insights. With this method, students become more active, creativity, and can receive lessons easily. Although the descriptive text is not too difficult, there are still many students who find it difficult. The purpose of this study was to determine the students' ability in writing descriptive texts with the mind mapping method and to find out how teachers teach descriptive texts. This is qualitative research. In collecting data, the researcher used text analysis and observation. The writing components analyzed were idea development, idea organization, grammar, vocabulary, and punctuation. The results of this study illustrate that the mind mapping method helps improve students' ability in writing descriptive texts, as can be seen from the way students develop ideas and organize ideas into a paragraph. Behind all that, the researcher also found the students' biggest difficulties in writing descriptive texts. Difficulties in grammar, vocabulary, and mechanics also have errors, but the errors are not significant.